Transthoracic echocardiography-guided subaortic ventricular septal defect closure in infants: a case report - Prakoso, Radityo; Ariani, Rina; Kurniawati, Yovi; Mendel, Brian; Lilyasari, Oktavia (Frontiers in Cardiovascular Medicine, 2025)
IntroductionSubaortic VSD, while similar to perimembranous defects, pose a higher risk for aortic valve insufficiency and AV block. This case aims to assess the safety and efficacy of percutaneous subaortic VSD closure in infants under 10 kg using transthoracic echocardiography-only guidance.Case presentationA one-year-old infant, 8.9 kg, was scheduled for subaortic VSD closure due to concerns of failure to thrive. Percutaneous closure was performed using a retrograde transarterial approach with a 7/5 mm Konar-MF VSD Occluder (Lifetech) under TTE guidance. Apical 5-chamber view showed smallest VSD diameter 3.8 mm. 3.5/5F Guiding JR catheter with soft hydrophilic wire were then maneuvered to descending aorta in subxiphoid 12 o'clock view, suprasternal short axis view and positioned just above the aortic valve. Catheter was then entered to the LV shown by parasternal long axis view. 3.5/5F Guiding JR catheter was then crossed the subaortic VSD in parasternal short axis view. The Konar-MF VSD Occluder (Lifetech) No. 7/5 mm was deployed assisted by apical 5-chamber view. Device detachment was then evaluated in parasternal short axis view showing no residual shunt. At six-month follow-up, the device was well seated, and the symptoms subsided.ConclusionsOur case underscores that zero-fluoroscopy TTE-only percutaneous subaortic VSD closure is feasible in selected patients under 10 kg with no major complications.